THE EFFECT OF WORK DISCIPLINE AND WORK STRESS ON EMPLOYEE LOYALTY AT THE PUBLIC WORKS AND SPATIAL PLANNING OFFICE OF TANAH DATAR REGENCY - Angela, Marissa Nur; Yuswardi, Arif; Aima, M. Havidz; Lusiana, Lusiana (Gapenas Publisher, 2025)
This study aims to analyze the influence of work discipline and work stress on employee loyalty at the Public Works and Spatial Planning Office of Tanah Datar Regency. The research method used is quantitative with a survey approach using questionnaires. The number of respondents was 53 employees of the Public Works and Spatial Planning Office of Tanah Datar Regency. Data analysis is carried out in several stages, namely 1)The Validity Test is tested by Pearson correlation (r count > r table). 2) Reliability tested with Cronbach Alpha (> 0.60 is considered reliable). 3) Normality Test to find out whether the data is normally distributed or not 4) T test to find out the influence of each independent variable on the dependent variable. 5) F test to determine the effect of work discipline and work stress simultaneously on employee loyalty. 6) Coefficient of Determination (R²) to find out how much contribution independent variables contribute in explaining dependent variables. Effective leadership, demonstrated by an exemplary attitude, open communication, and participatory decision-making, as well as a conducive work culture such as discipline, responsibility, and teamwork, has been proven to be able to improve employee productivity and work quality. This research makes a theoretical and practical contribution in efforts to improve the performance of local government apparatus. This study aims to analyze the influence of work discipline and work stress on employee loyalty at the Public Works and Spatial Planning Office of Tanah Datar Regency. The research method used is quantitative with a survey approach using questionnaires. The number of respondents was 53 employees of the Public Works and Spatial Planning Office of Tanah Datar Regency. Data analysis is carried out in several stages, namely 1)The Validity Test is tested by Pearson correlation (r count > r table). 2) Reliability tested with Cronbach Alpha (> 0.60 is considered reliable). 3) Normality Test to find out whether the data is normally distributed or not 4) T test to find out the influence of each independent variable on the dependent variable. 5) F test to determine the effect of work discipline and work stress simultaneously on employee loyalty. 6) Coefficient of Determination (R²) to find out how much contribution independent variables contribute in explaining dependent variables. Effective leadership, demonstrated by an exemplary attitude, open communication, and participatory decision-making, as well as a conducive work culture such as discipline, responsibility, and teamwork, has been proven to be able to improve employee productivity and work quality. This research makes a theoretical and practical contribution in efforts to improve the performance of local government apparatus.